Visualizations of macroevolutionary timescales - Stenlund, Jörgen (Linköping University, 2018)
Data consisting of animations of different temporal aspects of hominin evolution.

The aim of the study was to investigate how various representations of time in an animation affect the way undergraduate students comprehend different temporal aspects of hominin evolution. Two factors, differences in timelines (the number of timelines with different scales) and the mode of the default animated time rate– either constant throughout the animation or decreasing as the animation progressed – were combined to give four different time representations.

The animations are designed as a map on which animated areas are superimposed. Each area represented the appearance, dispersal and disappearance of a chosen sample of different species, or groups of species in hominin evolution. All animations are three-and-a-half minute long. These features are shared by all versions of the animation. The only difference between the various animations is how time is represented. The visual representation of time is located below the map and consists of two components: one or several timelines with different scales, and an animated cursor moving horizontally along the timeline, indicating current time and rate of time in the animation.

Description of the different temporal representations in the animations:

Animation A One timeline and a constant time rate.

Animation B One timeline and a time rate that decreases as the animation approach present time.

Animation C three emerging timelines of increasing scales become visible as the animation approach present time and a constant time rate.

Animation D three emerging timelines of increasing scales become visible, and a time rate that decreases as the animation approach present time.

NOTE: Using Macintosh computer and the Safari web browser might cause an error loading the videos. In order to guarantee the video function in Macintosh computers, please use another web browser such as Chrome, FireFox or Opera.

The dataset was originally published in DiVA and moved to SND in 2024.

Data innehåller animationer av olika tidsaspekter av homininernas utveckling.
OBS: Om du använder en Macintosh-dator och webbläsaren Safari kan det uppstå ett fel vid inläsningen av videorna. För att garantera videofunktionen i Macintosh-datorer, vänligen använd en annan webbläsare som Chrome, FireFox eller Opera.

Se engelsk beskrivning för mer info.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Visualizations of macroevolutionary timescales
Keywords: animation; animation; Hominoidea; människoapor; evolution; evolution; visualisation; visualisering; Pan (hominids); schimpanser (släkte); Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Zoology; Zoologi; Evolutionary Biology; Evolutionsbiologi